A story of "communities": boundaries, geographical composition and social coherence in a forest conservation project, Northern Cambodia. Issue 2 (2nd July 2016) - Pasgaard, Maya; Nielsen, Tania Fredborg
Abstract: Explicit notions of "communities", as key actors in conservation and development projects across the Global South, are common. Narratives about "indigenous people" or "forest-dependent communities" in forest conservation programmes prevail, portraying a picture of "communities" as homogeneous and harmonious entities. In this study, we unfold "communities" as a construct with an empirical example of a community-based forest protection project, Northern Cambodia. Based on qualitative interviews, field observations and document analysis, we examine the "community" construct in terms of establishment of boundaries, geographical composition and social coherence. We not only find that the establishment of forest "community" boundaries are dominated by powerful external actors rather than the "community members" themselves, but that the spatial composition of "communities" is complex, and affects the ability of local people to benefit from the project. We also find that the studied "communities" show low levels of social coherence and mainly consist of migrant farmers, as opposed to common policy narratives. Taking these inconsistencies into account, we discuss implications of constructing "communities" for the success of forest conservation projects, and argue in favour of more discursive and political analyses to better understand, acknowledge and adapt to existing and changing conditions in present and prospective project locations.